IMPLEMENTASI PEMBANGUNAN PARTISIPATIF (Studi Kasus Di Kelurahan Andowia Kabupaten Konawe Utara) - Puspita Sari, Ita (JURNAL EKONOMI UHO, 2016)
The purposes of this study were: (1) to determine the implementation of participatory development; (2) to determine factors that affected people’s level of participation in the development. The study was conducted at the village of Andowia, in the subdistrict of Andowia, North Konawe Regency, in November 2015. Informant were determined using a purposive random sampling technique, that is, by deliberately choosing 22 informants. Data were obtained using observation and interview, and were analyzed descriptively and qualitatively. Results of the study showed that overall the implementation of participatory development in the village of Andowia has been dissatisfactory, due to a lack of people’s participation in meetings that discussed the process of development in the village of Andowia. Among the factors that affected the level of people’s participation in the development of Andowia village were the supporting factors, which included awareness/willingness, people’s participation, and supports from the government and the people, and the hindering factors which included low quality of education, low incomes, and limited employment in the village.